Cell envelope gene expression in phosphate-limited Bacillus subtilis cells. - BOTELLA, ERIC; DEVINE, KEVIN; HOKAMP, KARSTEN (My University, 2011)
The high phosphate content of Bacillus subtilis cell walls dictates that cell wall metabolism is an important feature of the PhoPR-mediated phosphate limitation response. Here we report the expression profiles of cell-envelope-associated and PhoPR regulon genes, determined by live cell array and transcriptome analysis, in exponentially growing and phosphate-limited B. subtilis cells. Control by the WalRK two-component system confers a unique expression profile and high level of promoter activity on the genes of its regulon with yocH and cwlO expression differing both qualitatively and quantitatively from all other autolysin-encoding genes examined. The activity of the PhoPR two-component system is restricted to the phosphate-limited state, being rapidly induced in response to the cognate stimulus, and can be sustained for an extended phosphate limitation period. Constituent promoters of the PhoPR regulon show heterogeneous induction profiles and very high promoter activities. Phosphate-limited cells also show elevated expression of the actin-like protein MreBH and reduced expression of the WapA cell wall protein and WprA cell wall protease indicating that cell wall metabolism in this state is distinct from that of exponentially growing and stationary-phase cells. The PhoPR response is very rapidly deactivated upon removal of the phosphate limitation stimulus with concomitant increased expression of cell wall metabolic genes. Moreover expression of genes encoding enzymes involved in sulphur metabolism is significantly altered in the phosphate-limited state with distinct perturbations being observed in wild-type 168 and AH024 (ΔphoPR) cells.
PUBLISHED
Keywords: Bacillus subtilis.